2019
DOI: 10.1097/jd9.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Papillon-Lefèvre Syndrome: A Case Report

Abstract: Introduction: Papillon-Lefèvre syndrome (PLS) is an autosomal recessive disorder characterized by a diffuse palmoplantar hyperkeratosis and early periodontal destruction. Only a few PLS cases are reported by dermatological clinicians due to its rarity.Here, we reported a 16-year-old Chinese boy presented with diffuse transgradient palmoplantar hyperkeratosis since 4 years of age.Case presentation: The patient had also experienced recurrent episodes of swollen gums with premature loss of teeth. He is treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In homozygous PLS patients with cathepsin C gene mutations, loss of function has been identified [ 4 ]. This gene is abundantly expressed in immune defence cells and epithelial tissues, particularly in gingiva and the ventral skin surfaces of hands as well as feet [ 5 ]. Toomes et al believed PLS had a strong genetic basis and their research has shown that patients with PLS exhibited amorphic mutations that affected the alleles of the cathepsin C gene, a lysosomal protease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In homozygous PLS patients with cathepsin C gene mutations, loss of function has been identified [ 4 ]. This gene is abundantly expressed in immune defence cells and epithelial tissues, particularly in gingiva and the ventral skin surfaces of hands as well as feet [ 5 ]. Toomes et al believed PLS had a strong genetic basis and their research has shown that patients with PLS exhibited amorphic mutations that affected the alleles of the cathepsin C gene, a lysosomal protease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toomes et al believed PLS had a strong genetic basis and their research has shown that patients with PLS exhibited amorphic mutations that affected the alleles of the cathepsin C gene, a lysosomal protease [ 6 ]. Cathelicidin antimicrobial peptide LL-37, which was found diminished in the gingival crevicular fluid and neutrophils of PLS patients, is produced by proteinase 3 and is essential for the production of cathepsin C [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the genetic mutations linked to this disorder may explain the immune perturbations and provide novel information useful for identification of therapeutic targets. Finally, a case report by Zhao et al 6 highlights the clinical and histopathological features of a young patient with Papillon-Lefèvre syndrome, a rare autosomal recessive disorder. The authors also reported improvement of skin lesions following treatment with oral retinoids and antibiotics.…”
mentioning
confidence: 99%